CRISPR/Cas9: a sustainable technology to enhance climate resilience in major Staple Crops - Kaur, Navjot; Qadir, Muslim; Francis, Dali V.; Alok, Anshu; Tiwari, Siddharth; Ahmed, Zienab F. R. (Frontiers in Genome Editing, 2025)
Climate change is a global concern for agriculture, food security, and human health. It affects several crops and causes drastic losses in yield, leading to severe disturbances in the global economy, environment, and community. The consequences on important staple crops, such as rice, maize, and wheat, will worsen and create food insecurity across the globe. Although various methods of trait improvements in crops are available and are being used, clustered regularly interspaced short palindromic repeats and CRISPR-associated protein 9 (CRISPR/Cas9) mediated genome manipulation have opened a new avenue for functional genomics and crop improvement. This review will discuss the progression in crop improvement from conventional breeding methods to advanced genome editing techniques and how the CRISPR/Cas9 technology can be applied to enhance the tolerance of the main cereal crops (wheat, rice, and maize) against any harsh climates. CRISPR/Cas endonucleases and their derived genetic engineering tools possess high accuracy, versatile, more specific, and easy to design, leading to climate-smart or resilient crops to combat food insecurity and survive harsh environments. The CRISPR/Cas9-mediated genome editing approach has been applied to various crops to make them climate resilient. This review, supported by a bibliometric analysis of recent literature, highlights the potential target genes/traits and addresses the significance of gene editing technologies in tackling the vulnerable effects of climate change on major staple crops staple such as wheat, rice, and maize.